6-deoxy-6-amino chitosan: a preventative treatment in the tomato/Botrytis cinerea pathosystem - Moola, Naadirah; Jardine, Anwar; Audenaert, Kris; Rafudeen, Mohamed Suhail (Frontiers in Plant Science, 2023)
6-deoxy-6-amino chitosan (aminochitosan) is a water-soluble chitosan derivative with an additional amine group at the C-6 position. This modification has improved aqueous solubility, in vitro antifungal activity and is hypothesized to have enhanced in vivo antifungal activity compared to native chitosan. Gray mold disease in tomatoes is caused by the fungus, Botrytis cinerea, and poses a severe threat both pre-and post-harvest. This study aimed to investigate the antifungal and priming properties of aminochitosan and its lower molecular weight fractions and delineate the optimal concentrations for in vitro and in vivo use in the tomato/B. cinerea pathosystem. Despite batch-to-batch variations in aminochitosan, it displayed significantly greater inhibition of B. cinerea in vitro than native chitosan at a minimum concentration of 1 mg/mL. A concentration-dependent increase in the in vitro antifungal activities was observed for radial growth, sporulation, and germination with maximum in vitro inhibition for all the biopolymer batches in general, and lower MW fractions at 2.5 and 5 mg/mL, respectively. However, the inhibition threshold for aminochitosan was identified as 1 mg/mL for spores germinating in vivo, compared to the 2.5 mg/mL threshold in vitro. The pre-treatment of leaves with aminochitosan displayed efficacy in priming direct and systemic resistance to B. cinerea infection 4, 6 and 30 days post-inoculation by maintaining elevated PSII activity (Fv/Fm) and chlorophyll content (ChlIdx) due to a stronger and more rapid elicitation of the defense systems at earlier time points. However, these defense systems appear to be ROS-independent at higher concentrations (1 and 2.5 mg/mL). In addition, aminochitosan accumulates in the cell membrane and therefore acts to increase the membrane permeability of cells after foliar spray. These observations corroborate the notion that aminochitosan biopolymers can exert their effects through both direct mechanisms of action (MOA) and indirect immunostimulatory mechanisms. The contrast between in vitro and in vivo efficacy highlights the bimodal MOA of aminochitosan and the advantageous role of primed plant defense systems.Characterization of 6-deoxy-6-amino chitosan as a preventative treatment in the tomato/Botrytis cinerea pathosystem